X-ray, IR, NMR, UV-visible spectra and DFT analysis of 5-aryloxy-(1H)-tetrazoles, structure, conformation and tautomerism - Pesyan, Nader Noroozi; Bavafa, Sadeghali; Enayati, Mohammad Samim; Hoseinpour, Sajedin; Ostadhosseini, Narges; Dadrass, Alireza; Soleimannejad, Jannet; Sahin, Ertan; Mohamed Tahir, Mohamed Ibrahim (Growing Science, 2014)
The predominant tautomeric forms of N1–H, N2–H of 5-(2,6-dimethyl- and 5-(2,6-diisopropylphenoxy)-(1H)-tetrazoles were analyzed at B3LYP method using 6-311G(d,p) basis set in the gas phase. The N1–H form of tetrazoles was found to be more stable than N2–H form in both solid and gas phases. Crystal structures of both tetrazoles show an intermolecular H-bond between N1-H and N4 atom of other tetrazole space. The hydrogen bonds between each tautomer of tetrazoles were evaluated at B3LYP/6-311G(d,p) level. The geometrical parameters and spectral data of tetrazoles and their variation were studied in both solid and gas phases.